2012
DOI: 10.1038/ng.1081
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies a variant in HDAC9 associated with large vessel ischemic stroke

Abstract: Genetic factors have been implicated in stroke risk but few replicated associations have been reported. We conducted a genome-wide association study (GWAS) in ischemic stroke and its subtypes in 3,548 cases and 5,972 controls, all of European ancestry. Replication of potential signals was performed in 5,859 cases and 6,281 controls. We replicated reported associations between variants close to PITX2 and ZFHX3 with cardioembolic stroke, and a 9p21 locus with large vessel stroke. We identified a novel associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
266
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 373 publications
(274 citation statements)
references
References 30 publications
7
266
1
Order By: Relevance
“…13,14,[35][36][37] Importantly, in the largest meta-analysis to date, all associations were with ischaemic stroke subtypes, and these showed much stronger association than in an analysis with all ischaemic stroke (κ = 1.24, 1.23, 1.19, and 1.11 for rs2107595 (HDAC9), rs6843082 (PITX2), rs879324 (ZFHX3), and rs2383207 (9p21), respectively). 13 Further to this, analyses of early onset cases suggest even stronger associations with young onset cases at these loci.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…13,14,[35][36][37] Importantly, in the largest meta-analysis to date, all associations were with ischaemic stroke subtypes, and these showed much stronger association than in an analysis with all ischaemic stroke (κ = 1.24, 1.23, 1.19, and 1.11 for rs2107595 (HDAC9), rs6843082 (PITX2), rs879324 (ZFHX3), and rs2383207 (9p21), respectively). 13 Further to this, analyses of early onset cases suggest even stronger associations with young onset cases at these loci.…”
Section: Discussionmentioning
confidence: 91%
“…Second, such clinical diagnoses ignore underlying heterogeneity in disease pathogenesis where case subtyping might be more appropriate. Examples of diseases with genetically distinct subgroups include ischaemic stroke, where at least three distinct pathologies (cardioembolic, small vessel and large vessel) lead to stroke events; 13,14 migraine, where cases with or without aura have distinct genetic susceptibility factors; 15 and rheumatoid arthritis, where anti-citrullinated peptide antibody-negative individuals show distinct genetic associations, particularly in the HLA region. 16,17 Third, heterogeneity in genetic susceptibility to disease may exist.…”
Section: Introductionmentioning
confidence: 99%
“…49 Moreover, a recent genome-wide association study found two single nucleotide polymorphic (SNP) variants of HDAC9 to be strongly linked to large blood vessel disease in humans. 50 These findings raise the intriguing possibility that therapeutically targeting HDAC9 in obesity could also favorably modulate the development of cardiovascular complications, a major cause of morbidity and mortality in this population.…”
Section: Hdac9 As a Potential Therapeutic Target In Obesity: Present mentioning
confidence: 99%
“…SNP data for these samples were available from a recent genome-wide association study using the Affymetrix SNP Array 6.0 as previously described (Bellenguez et al 2012).…”
Section: Genotypingmentioning
confidence: 99%